Holy and Worldly... Body, Somatic Dimension of Narration - Lis-Wielgosz , Izabela (Poznańskie Studia Slawistyczne, 2020)
The article briefly presents a series of problems discussed in the dissertation entitled Свето и пропадљиво. Тело у српској хагиографској књижевности (Holy and Worldly. Body in Serbian Hagiographic Literature) by Smilja Marjanović-Dušanić. Dedicated to a wide professional and non-professional audience, the book in question is a significant scientific work since it refers not only to the historical, but also to the anthropological and culturological description related to the activity of decoding of such essential socio-cultural category like body. Considered as a highly complex phenomenon, body is a sign generated by the realm of various traditions and discourses which render different cultural modes or primary and secondary contexts; it might be also conceived as a distinctive signature of given time-space, community and cultural system. It will not be an exaggeration to say that the dissertation is an extremely interesting and indeed outstanding study of the subject which impresses with its high cognitive value and research rank. What is more, it offers a serious and objective view of the convoluted and multidimensional cultural phenomenon and identity construct.